Food for the Soul, Bodies for Virtue. On Porphyry’s Vegetarianism in De Abstinentia - Costero-Quiroga, Sonsoles (2025)
“Food for the Soul, Bodies for Virtue. On Porphyry’s Vegetarianism in De Abstinentia”. This paper examines the treatise De Abstinentia ab esu animalium by the Neoplatonic philosopher Porphyry, with a focus on the figure of the philosopher-priest. This figure is characterized as one who strives to attain an ascetic lifestyle through adherence to certain precepts, including the performance of humble sacrifices to the gods, abstention from animal-derived foods, the practice of austerity in all aspects of life, and the cultivation of that what is truly important: the purification (kátharsis) of the soul and the assimilation to the divine (homoí?sis the?i). Furthermore, this article explores the arguments presented by Porphyry to promote a positive model for the individual subject. It also discusses how a choice of life based on dietary restrictions and an ethic of self-control can be seen not only as a path to divinity but also as a defining characteristic of the true philosopher—namely, one who establishes himself as a model worthy of emulation (the?os anér). This perspective highlights the role of the philosopher-priest as both an active follower and adherent of philosophy and a living example of virtue and wisdom, serving as an ethical reference point that inspires others to emulate this ideal and to reflect on our own daily practices.